Infestation rate and impacts of Epipenaeon ingens on growth and reproduction of brown shrimp (Penaeus aztecus) - Gokoglu, Mehmet; Teker, Serkan; Korun, Jale (Acta Aquatica: Aquatic Sciences Journal, 2020)
In this study, 515 Farfantepenaeus aztecus specimens were investigated in the Gulf of Antalya and 304 (59,02%) specimens (167 females and 137 males) infested with Bopyrid isopod parasite Epipenaeon ingens were found. In this study, we aimed to define the rate of infestation and its impact on survival rate and growth rate. Relationship of length- weight and condition factor values were lower in infested specimens compared to non-infested ones. While gonadal development was observed in different stages of non-infested female specimens, no gonadal development was observed in any infested specimens. Moreover, darker color and harder shell structure were observed in parasitized shrimps. During this research, infestation onto P. semisulcatus and P. kerathurus had been seen rarely.Keywords: Gulf of Antalya; Epipenaeon ingens, Farfantepenaeus aztecus; growth; reproduction